Frequent Mutational Activation of the PI3K-AKT Pathway in Trastuzumab-Resistant Breast Cancer - Sarat Chandarlapaty; Rita A. Sakr; Dilip D. Giri; Sujata Patil; Adriana Heguy; Monica Morrow; Shanu Modi; Larry Norton; Neal Rosen; Clifford A. Hudis; Tari A. King (2012)
Abstract Purpose: HER2-amplified breast cancer is sometimes clinically insensitive to HER2-targeted treatment with trastuzumab. Laboratory models of resistance have causally implicated changes in HER2 expression and activation of the phosphoinositide 3-kinase (PI3K)–AKT pathway. We conducted a prospective tissue acquisition study to determine if there is evidence for these lesions in metastatic tumors that have progressed on trastuzumab-containing therapy. Experimental Design: From 2/2007 to 11/2011, 63 patients with HER2-amplified breast cancer with recurrence of disease after adjuvant trastuzumab therapy or World Health Organization–defined progression of metastatic disease on a trastuzumab-containing regimen were prospectively enrolled and underwent tumor biopsy. Specimens were analyzed for activating mutations in PIK3CA and HER2 by Sequenom and analyzed for HER2 and PTEN status by immunohistochemistry. Results: In 53/60 cases (88%, 3 cases not evaluable for HER2), HER2 overexpression persisted in the metastatic tumor following trastuzumab exposure. Among the 7 cases lacking HER2 overexpression, repeat analysis of the pretreatment tumor failed to confirm HER2 overexpression in five cases. Among cases evaluable for PTEN (56) or PI3K mutation (45), absent or significantly diminished PTEN expression was noted in 33 (59%) and activating mutations in PIK3CA in 13 (29%). The combined rate of PTEN loss and PIK3CA mutation in the trastuzumab-refractory tumors was 71% compared with 44% (P = 0.007) in an unexposed cohort of 73 HER2-amplified tumors. Conclusions: In this series of prospectively collected trastuzumab-refractory human breast cancers, loss of HER2 overexpression was rare, whereas activation of the PI3K-AKT pathway through loss of PTEN or PIK3CA mutation was frequently observed. Clin Cancer Res; 18(24); 6784–91. ©2012 AACR.